1997
DOI: 10.1097/00004872-199715110-00011
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum parathyroid hormone levels in the elderly and 24 h ambulatory blood pressures

Abstract: Serum PTH levels are related strongly to the blood pressure, particularly the nocturnal blood pressure in the elderly. It is not known whether PTH levels are a consequence or a cause of the elevation in blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 10 publications
2
29
1
3
Order By: Relevance
“…38 We also found that BP Ͼ130/80 mmHg was independently related to higher PTH levels. Such a cross-sectional association is also reported in patients without CKD, 39 but establishing the existence of causality would require a prospective investigation. For hyperphosphatemia, the GFR threshold at diagnosis was 37 ml/min per 1.73 m 2 , consistent with results from the SEEK study, which used a slightly higher cutoff (1.48 mmol/L).…”
Section: Discussionmentioning
confidence: 82%
“…38 We also found that BP Ͼ130/80 mmHg was independently related to higher PTH levels. Such a cross-sectional association is also reported in patients without CKD, 39 but establishing the existence of causality would require a prospective investigation. For hyperphosphatemia, the GFR threshold at diagnosis was 37 ml/min per 1.73 m 2 , consistent with results from the SEEK study, which used a slightly higher cutoff (1.48 mmol/L).…”
Section: Discussionmentioning
confidence: 82%
“…Gennari et al (25) also found simultaneous increases in PTH and urinary calcium excretion and suggested that high levels of serum sodium in patients with essential hypertension may have been due to excessive dietary salt intake or a defect in the excretion of sodium, which leads to excessive calcium excretion (8,15,19,25,26). In agreement with the significant effect of renal dysfunction on PTH elevation reported in these previous studies, in the present study, sodium levels and urinary calcium levels were determined to be positively and significantly correlated with PTH, ASBP, and ADBP (p=0.001, for each) in our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, a relationship between hyperparathyroidism with LVH and BP elevation has been demonstrated in hypertensive patients (1,(12)(13)(14). However, whether the increase in PTH level is the result of or the reason for the BP elevation has not been elucidated (15). In addition, it has been reported that PTH increases cytosolic free calcium, and this might cause myocardial hypertrophy through biochemical mechanisms (16).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated PTH secondary to low vitamin D increases calcium resorption from the skeleton at the expense of an increased risk of fracture (20). Secondary hyperparathyroidism may also increase the risk of developing components of metabolic syndrome, including hypertension (21)(22)(23)(24)(25)(26), obesity (6,9,10,(27)(28)(29), and diabetes (30 -32). However, we are unaware of previous research investigating whether PTH levels are also associated with the metabolic syndrome.…”
mentioning
confidence: 99%